Abrasive wear behaviour of Al–SiC composites produced by pressure infiltration technique - Candan, Ercan; Ahlatci, Hayrettin; Cimenoglu, Huseyin (Elsevier BV, 2001)
Abstract In this study, abrasive wear behaviours of compacts produced by pressure infiltration technique were investigated. Pure aluminium and SiC particles having 13 and 37 μm mean diameters were used in the infiltration process. The volume fraction of the SiC particles was 60% in the compacts. Abrasive wear tests were carried out under the normal load of 28 N, by rubbing the compacts to abrasive Al2O3 grains with diameters in the range of 85–250 μm. Wear tests revealed that, the effect of the size of SiC particles on the wear resistance of compacts, depends on the size of the Al2O3 abrasive grains being rubbed. The compact which had 13 μm SiC particles exhibited higher wear rate than the compact having 37 μm SiC particles when rubbed on fine abrasive Al2O3 grains (
Keywords: nano-technology; engineering and technology